Thematic Analysis Of Arabic Language Curriculum Integration Of Multidimensional Values Scopus Indexed Literature Review - Ilya Husna; Yasmadi Yasmadi; Rahmawati Rahmawati; Afrina Refdianti; Isra Hayati Darman; Ira Aniati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to map research trends in Arabic language curriculum development, based on twelve scholarly articles indexed in the Scopus database and published between 2014 and 2025. The study employs a systematic literature review approach, grounded in Arlene Fink’s framework, which comprises three main stages: literature sampling, literature screening, and data extraction. The selected articles met specific inclusion criteria relevant to the theme of Arabic curriculum development in the context of contemporary education. The data extraction process focused on four key elements of each article: authorship, research objectives, methods, and findings. Thematic analysis of these articles identified five central themes in curriculum development: the integration of environmental values, the incorporation of local wisdom, the integration of spiritual aspects, the enhancement of creativity through curriculum design, and the urgency of formulating a more adaptive and contextual national curriculum standard. These thematic findings are further analyzed through the lens of William Pinar’s reconceptualist curriculum theory, which views curriculum not merely as a technical instructional tool, but as a subjective, reflective, and cultural process (currere). The study reveals that the Arabic language curriculum in Indonesia remains normative and is not yet fully responsive to local and global dynamics. Accordingly, this research recommends the development of a more collaborative, contextual, and holistically oriented Arabic language curriculum. It is expected that this study will serve as a significant reference for policymakers and curriculum developers in designing an Arabic curriculum that is relevant, responsive, and transformative.